PENGATURAN JAM OPERASIONAL BAGI TRUK PENGANGKUTAN BARANG UNTUK KESELAMATAN PENGGUNA JALAN DI KABUPATEN NUNUKAN: Regulation of Operating Hours for Freight Trucks for the Safety of Road Users in Nunukan Regency - Della Amalia Silawane; Siti Nurbaiti (Reformasi Hukum Trisakti, 2025)
Dynamic economic development and increasing vehicle volume present increasingly critical transportation safety challenges, related to freight transport vehicles that cause serious accidents. One example is an accident involving a freight truck that indicates a violation of truck operating hours that has the potential to increase road accidents. The problem formulation in this study is How are the operating hours for freight trucks regulated for the safety of road users in Nunukan Regency? This study uses a normative method, which is descriptive in nature with secondary data as the source and primary data as supporting secondary data. Data analysis was conducted qualitatively with deductive conclusions drawn. The results of the discussion and conclusions of this study illustrate that the regulation of operating hours for freight trucks for the safety of road users in Nunukan Regency has not been regulated in Nunukan Regency Regional Regulation Number 9 of 2014 because there has not been a determination of road classes. The lack of regulations regarding truck operating hours is the cause of the high number of accidents. Therefore, more detailed regulations regarding truck operating hours and strict supervision are needed to improve traffic safety.